A climate-informed, ecosystem approach to fisheries management. (July 2015) - Heenan, Adel; Pomeroy, Robert; Bell, Johann; Munday, Philip L.; Cheung, William; Logan, Cheryl; Brainard, Russell; Yang Amri, Affendi; Aliño, Porfirio; Armada, Nygiel; David, Laura; Rivera-Guieb, Rebecca; et al.
Abstract: This paper outlines the benefits of using the framework for an ecosystem approach to fisheries management (EAFM) for dealing with the inevitable yet unclear impacts of climate change and ocean acidification on coastal fisheries. With a focus on the Asia-Pacific region, it summarizes the projected biological and socio-economic effects of increased emissions of carbon dioxide (CO2 ) for coastal fisheries and illustrates how all the important dimensions of climate change and ocean acidification can be integrated into the steps involved in the EAFM planning process. The activities required to harness the full potential of an EAFM as an adaptation to climate change and ocean acidification are also described, including: provision of the necessary expertise to inform all stakeholders about the risks to fish habitats, fish stocks and catches due to climate change; promotion of trans-disciplinary collaboration; facilitating the participation of all key stakeholders; monitoring the wider fisheries system for climate impacts; and enhancing resources and capacity to implement an EAFM. By channeling some of the resources available to the Asia-Pacific region to adapt to climate change into an EAFM, developing countries will not only build resilience to the ecological and fisheries effects of climate change, they will also help address the habitat degradation and overfishing presently reducing the productivity of coastal fisheries. Highlights: The biological and socio-economic effects of climate and ocean change on fisheries in the Asia-Pacific are summarized. The benefits of an ecosystem approach to fisheries to manage for climate and ocean change are outlined. Activities to integrate into the development of an ecosystem-based fisheries management plan are described.